Sarcoptes Infestation. What Is Already Known, and What Is New about Scabies at the Beginning of the Third Decade of the 21st Century? - Katarzyna Talaga-Ćwiertnia (Pathogens, 2021)
Currently, there are three known subtypes of scabies: ordinary, crusted, and bullous. The worldwide prevalence of scabies remains high in the 21st century. To decrease the social, economic, and psychological impact on the enormous population infected, a lot of important work has been completed over the last 20 years concerning the management of scabies. For example, a standardization of guidelines for the treatment of scabies has been completed and programs have been designed for the prevention and treatment in endemic populations, called mass drug administrations. Unfortunately, these only apply to the ordinary form of scabies. Moreover, resistance to the drugs currently used in treatment is growing, which imposes the need to search for new treatments. For this purpose, new acaricides are being developed to enhance the therapeutic options for the patients’ benefit and effectively treat this disease. There is also the necessity for prevention before the development of scabies. An effective vaccine has the potential to protect people before this disease, especially in endemic areas. Unfortunately, there are no such vaccines against Sarcoptes yet.